Optimalisasi Kesehatan Mental dalam Upaya Meningkatkan Rasa Percaya Diri pada Mahasiswa PSIK UIN Jakarta - Nazwa Rafa Nurfadhilah; Dara Suci Hernata; Tantri Rivakalebbi Ibrahim; Dwi Setyowati (IAHN Gde Pudja Mataram, 2022)
The Covid-19 pandemic that occurred from 2020 to 2022 compelled the government to make a variety of efforts to reduce the spread of COVID-19 in Indonesia, one of which was the implementation of online learning for higher education through the Government Ministry of Education and Culture. Online learning has an impact on students' confidence in discussing, expressing opinions, and completing assignments and exams on their own. The goal of this study was to see if there was a decrease in self-confidence and mental health among Syarif Hidayatullah Jakarta State Islamic University Nursing students in 2021 as a result of online learning. The participants in this study were Nursing students from Syarif Hidayatullah State Islamic University Jakarta Batch 2021 with a total of 28 students. A qualitative descriptive research model underpins this research method. Data is collected using online tools such as Google Forms. The findings show that the majority of respondents had a level of confidence before the pandemic with a scale of 4 on a scale of 1-5 as many as 17 people (60.7 percent), while a minority of respondents had a level of confidence before the pandemic with a scale of 2 on a scale of 1-5 as many as 2 people (7.1 percent). According to the level of student confidence after the pandemic, the majority of respondents had a confidence level after the pandemic of 3 on a scale of 1-5, 13 people (46.4 percent), a minority of respondents, reported a level of confidence after the pandemic of 2 on a scale of 1-5. (17.9 percent ).